(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
America is one of the foremost western nations identified as having a free and just society. As such, the government must ensure that American citizens are receiving a fair and equitable education that prepares them to be effective citizens in a liberal democratic nation. One historical goal of public education in America is the transmission of culture from one generation to the next. However, in a globally diverse society education should not be limited to the reproduction of the dominant ideology, but should emphasize the promotion of those values that support a liberal democracy: protection from despots, the possession of fundamental political rights and liberties, and most importantly a pluralistic system in which they may self-determine what is best for their own good and interests.